Grassland ecology : an analysis of Wolf Totem from an ecological perspective. - Qiao Meng; Omar, Noritah (Canadian Academy of Oriental and Occidental Culture, 2011)
Much discussion has been done on Jiang Rong’s presentation of the national character of the Chinese in Wolf Totem, so that it overshadows an equally important aspect of the novel: the grassland ecology. Thus, we aim to contrast the different attitudes towards nature of the nomadic Mongols on the one pole, and the Han Chinese, the migrant and young Mongols on the other. Besides, we try to summarize the nomads’s ecosophy as reflected in the novel. Ecotheory, especially Arne Naess’ ecosophy T offers a very efficient tool for our exploration. One problem yet to be solved, however, is the regression of the traditional ecosophy engendered by the challenges from different social forces such as politics and economy. Thus, how to preserve the traditional positive ecosophy needs efforts from all parties apart from the ecologists.